Adolescent Distal Humerus Fractures: ORIF Versus CRPP. Issue 8 (December 2017) - Bell, Phillip; Scannell, Brian P.; Loeffler, Bryan J.; Brighton, Brian K.; Gaston, R. Glenn; Casey, Virginia; Peters, Melissa E.; Frick, Steven; Cannada, Lisa; Vanderhave, Kelly L.
Abstract : Background: Although supracondylar humerus fractures are common in young children, the incidence in adolescents is much lower. As a result, there is a paucity of literature to guide treatment. The purpose of this study was to review the treatment and outcomes for a consecutive series of distal humerus fractures in adolescents and to compare outcomes between patients treated with percutaneous skeletal fixation and those treated with open reduction and fixation. Methods: A retrospective review of patients 10 to 17 years of age who underwent surgical treatment for a distal humerus fracture from 2005 to 2014 was performed. Patients with medial epicondyle fractures and those with insufficient follow-up to document union or return of motion were excluded. Medical records were reviewed to collect demographic data as well as operative approach and method of fixation. Clinical outcomes included range of motion, time to maximum motion, and complications [nerve dysfunction, heterotopic ossification (HO), need for secondary surgery]. Radiographs were reviewed to determine time to union as well as coronal and sagittal alignment. Results: One hundred eighteen adolescents with displaced distal humerus fractures were identified. Eighty-one met inclusion criteria. Forty-four of these were classified as extra-articular [Orthopaedic Trauma Association (OTA) 13-A], and 37 were intra-articular fractures (10 OTA 13-B and 27 OTA 13-C). Although not statistically significant, closed treatment with percutaneous fixation of extra-articular fractures resulted in greater flexion-extension arc of motion at final follow-up (128 vs. 119 degrees, P =0.17) and demonstrated more rapid return of motion (2.8 vs. 3.9 mo, P =0.05) when compared with open treatment despite a longer duration of immobilization and less formal physical therapy. Complications such as HO ( P =0.05), nerve dysfunction ( P =0.02), and secondary surgery ( P =0.001) were more common in the open treatment group. Closed treatment with percutaneous fixation of intra-articular fractures was performed in younger patients of similar size (12.8 vs. 14.4 y, P <0.01; 154 vs. 142 lbs, P =0.5). There were no significant differences between groups in regard to outcomes or complications. There were trends toward increased frequency of HO, nerve dysfunction, and secondary surgery in the open treatment group. Patients with intra-articular fractures were older (14.2 vs. 11.5 y, P <0.001) and heavier (144 vs. 94 lbs, P <0.001) than patients with extra-articular fractures and were more likely to be treated open (74% vs. 11%, P <0.001). Extra-articular fractures demonstrated a greater total arc of motion (126 vs. 118 degrees, P =0.04) at final follow-up despite longer duration of immobilization (23 vs. 15 d, P =0.002), and less physical therapy (27% vs. 73%, P <0.001). Radiographic carrying angle (16.6 vs. 22.3 degrees, P =0.08) and anterior humeral line (95% vs. 81%, P =0.07) trended toward more anatomic alignment in the extra-articular group. Secondary surgery was more common after intra-articular fracture (24% vs. 7%, P =0.03). Conclusions: Closed reduction and pinning of extra-articular distal humerus fractures in adolescents resulted in predictable clinical and radiographic outcomes and allowed for earlier return of motion and fewer complications when compared with open treatment. Intra-articular distal humerus fractures occur more frequently in older adolescents and are more likely to require open reduction and internal fixation to obtain joint congruity. Patients with intra-articular injuries should be cautioned that regaining full elbow motion may be more difficult, and there is an increased risk for complications and need for additional surgery. Closed reduction and percutaneous fixation of intra-articular injuries appears to be a reasonable option in select patients. Level of Evidence: Level III—retrospective comparative study.